CARA BARU PEMBUATAN TEMPE - Hermana Hermana; Sutedja Sutedja (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 1971)
Tjara baru pembuatan tempe. (The new method of preparing tempeh). Gizi Indonesia, 2 : 167, 1970. The new method of preparing tempeh involves dehulling of soybean by a burr mill, cooking in water up to the boiling point, soaking in the water used to boil for 22 hours, washing, and reboiling in fresh water. After draining, the beans were left to cool, followed by inoculation with tempeh mold inoculum and wrapping in cheese cloth for 24 hours. Fermentation for 14 to 16 hours were allowed after bagging the beans in perforated polyethylene film having pin-holes one in four square centimeters. Tempeh made by the new method was of milder aroma than traditional tempeh. The keeping quality was three days. On the third day the colour of tempeh remained white, changes in texture and aroma were slight. Dalam usaha untuk lebih mempopulerkan tempe, kami mencari cara pembuatan tempe yang: (1) sederhana, mudah dilakukan dengan kemungkinan gagal sekecil-kecilnya dan (2) menghasilkan tempe yang baik yang dapat disimpan lebih lama dari pada tempe tradisional.